Heme oxygenase-1 expression in human gliomas and its correlation with poor prognosis in patients with astrocytoma - Gandini, Norberto Ariel (2013)
In human glioma tumors, heme oxygenase-1 (HO-1) has been shown to be upregulated both when compared with normal brain tissues and also during oligodendroglioma progression. The cell types that express HO-1 have been shown to be mainly macrophages/microglia and T cells. However, many other reports also demonstrated that cell lines derived from glioma tumors and astrocytes express HO-1 after the occurrence of a wide variety of cell injuries and stressors. In addition, the significance of HO-1 upregulation in glioma had not, so far, been addressed. We therefore aimed at investigating the expression and significance of HO-1 in human glial tumors. For this purpose, we performed a wide screening of HO-1 expression in gliomas by using tissue microarrays containing astrocytomas, oligodendrogliomas, mixed tumors, and normal brain tissues. We subsequently correlated protein expression with patient clinicopathological data. We found differences in HO-1 positivity rates between non-malignant brain (22 %) and gliomas (54 %, p = 0.01). HO-1 was expressed by tumor cells and showed cytoplasmic localization, although 19 % of tumor samples also depicted nuclear staining. Importantly, a significant decrease in the overall survival time of grade II and III astrocytoma patients with HO-1 expression was observed. This result was validated at the mRNA level in a cohort of 105 samples. However, no association of HO-1 nuclear localization with patient survival was detected. In vitro experiments aimed at investigating the role of HO-1 in glioma progression showed that HO-1 modulates glioma cell proliferation, but has no effects on cellular migration. In conclusion, our results corroborate the higher frequency of HO-1 protein expression in gliomas than in normal brain, demonstrate that HO-1 is expressed by glial malignant cells, and show an association of HO-1 expression with patients’ shorter survival time.